2018
DOI: 10.1016/j.econlet.2017.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in cheating: Loss vs. gain framing

Abstract: Full bibliographic details must be given when referring to, or quoting from full items including the author's name, the title of the work, publication details where relevant (place, publisher, date), pagination, and for theses or dissertations the awarding institution, the degree type awarded, and the date of the award.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 18 publications
4
17
0
Order By: Relevance
“…For example, women demonstrated greater aversion toward lying for a small monetary benefit ( Childs, 2012 ) and lower dishonesty levels than men ( Friesen and Gangadharan, 2012 ). However, Ezquerra et al (2018) found no gender differences in a cheating game. It follows that men (or those who identify with the male role) who self-stereotype and embrace their gender role in-extremis will more likely try to assert their dominance at work.…”
Section: Literature Reviewmentioning
confidence: 87%
“…For example, women demonstrated greater aversion toward lying for a small monetary benefit ( Childs, 2012 ) and lower dishonesty levels than men ( Friesen and Gangadharan, 2012 ). However, Ezquerra et al (2018) found no gender differences in a cheating game. It follows that men (or those who identify with the male role) who self-stereotype and embrace their gender role in-extremis will more likely try to assert their dominance at work.…”
Section: Literature Reviewmentioning
confidence: 87%
“…However, various studies raise doubts about women's higher truthfulness. Some studies do not find evidence of gender differences in deceptive behavior at all (Childs, 2012;Ezquerra et al, 2018;Pate, 2018). Others find mixed evidence and discuss the potential impact of the gender composition of groups (Muehlheusser et al, 2015) or the implications of who benefits from a lie (Biziou- Van-Pol et al, 2015;Cappelen et al, 2013;Capraro, 2018;Dreber and Johannesson, 2008;Erat and Gneezy, 2012).…”
Section: Related Literaturementioning
confidence: 99%
“…In Table B3, we undertake the approach in Ezquerra, Kolev and Rodriguez-Lara (2018) to investigate whether there is cheating in each of the five treatments. Ezquerra, Kolev and Rodriguez-Lara (2018) consider a linear regression model where the dependent variable is the standardized die outcome;…”
Section: 99%mentioning
confidence: 99%